Pemikiran Nidhal Guessoum Dalam Integrasi Islam Dan Sains Modern: Implementasi Pada Pengembangan Modul Ajar IPA Untuk Kelas VII Tingkat Sekolah Menengah Pertama (SMP) - Damayanti, Anik, DR. Sudarno Shobron, M.Ag, Dr. Ari Anshori, M.Ag (2017)
This thesis is a research library with a philosophical approach. The method of analysis used descriptive and critical-analytic. This study aims to formulate two things, first probing Nidhal Guessoum in the integration of Islam and modern science. Researcher dug and reconstructed Guessoum's thought from his book "Islam's Quantum Question: Reconciling Muslim Tradition and Modern Science" into a formula to implement the integration of Islam and modern science in the field (the teaching of science in the classroom). Second, the researcher developed an integrated teaching module of Islam and modern science according to Guessoum's recommendation. The researcher concluded that there are three important components required in order to improve the teaching of science curriculum, namely: (1) the philosophy of science, (2) the history of science, (3) terraced reading the verses of the Qur'an related to science. Implementation of the integrated teaching module in this thesis, is by adding a third component into the existing teaching module of BSE. What is BSE? BSE is textbooks that are used widely by the people, by the quality of the content and presentation of the material already meets the standards of National Education. BSE is accessible free of charge for all Indonesian people because the copyright has been purchased by the Government through the Ministry of National Education. Development of an integrated teaching module is intended to provide convenience for science teachers in the classroom, which enhance the existing science material (BSE) by adding a third component which is recommended. Development of an integrated teaching module is ideally carried out by a team of educators in the field of science and expert/educator in the field of Islamic Studies, developing a science textbook teaching that is integrated with Islam. However, if an institution does not have this capability, then by applying the resulting formulation of this thesis, inshaAllah a science teacher can develop an integrated teaching module.